Non-Euclidean geometry a critical and historical study of its development - Bonola, Roberto 1874-1911; Carslaw, H.S.; Enriques, Federigo; Bolyai, János 1802-1860.; Lobachevskii, Nikolai Ivanovich 1793-1856. ([New York] Dover Publications, Inc., 1955)
Authorized English translation with additional appendices by H. S. Carslaw ; with an introduction by Federigo Enriques ; with a supplement containing the George Bruce Halsted translations of The science of absolute space, by John Bolyai [and] The theory of parallels, by Nicholas Lobachevski.
Includes bibliographical references.
Keywords: Geometry, Non-Euclidean.